Total phosphorus and phosphorus forms change in sediments along the Tone River - Kozyrev, Roman; Umezawa, Yu; Yoh, Muneoki (Frontiers in Earth Science, 2023)
Phosphorus (P) is an essential element for the metabolism, growth, and development of living organisms, and it often limits primary production in freshwater ecosystems. During flood events, rivers can transport considerable amounts of particulate organic P (org-P) and inorganic P from the basin to the ocean. Understanding the transport mechanisms and changes in P distribution from upstream to downstream areas of rivers is crucial to estimate its flux to the ocean. However, the processes involved in P transformation and cycling among different forms in rivers are not well understood. To better understand P transformation and total P (TP) concentrations in river basins, this study examined various P forms in bottom sediments, river bank sediments, parent rock material, and soil samples along the Tone River, Japan. P forms such as org-P, Ca-bound phosphorus (apatite, Ca-P), P bound with iron oxides/hydroxides (Fe-P), bio unavailable non-apatite inorganic P (NAIP), and TP were analyzed. The results showed an increase in TP concentration in bottom and bank sediment samples along the course of the Tone River. This change in TP was mostly due to the increases in Fe-P and bioavailable org-P, while Ca-P and NAIP decreased toward the downstream area. Analysis of parent rock in three main mountain group areas (Mount Tanigawa, Mount Akagi, and Mount Tsukuba) showed their downstream impacts on TP and the distribution of P forms. Sediment grain size distribution analysis suggested that Fe-P and org-P fractions increased with decreasing sediment particle size, while Ca-P and NAIP were relatively evenly distributed among all grain sizes. The data revealed the transformation of P forms in sediments of the largest river in the Kanto region, Japan, which influence its flux to the Pacific Ocean. The results suggest that Fe-P and org-P may play a more significant role in P transport from river basins to the ocean than previously thought. The findings of this study can be useful for estimating P fluxes to the ocean and for the management of freshwater ecosystems.